Prognostic role of baseline hemoglobin level for long-term mortality in newly diagnosed rheumatoid arthritis: a cohort study - Chen, I-Wen; Weng, Hsiu-Lan; Liao, Shu-Wei; Lai, Yi-Chen; Wang, Kuei-Fen; Wu, Jheng-Yan; Lin, Ming-Chung; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundPatients with rheumatoid arthritis (RA) face an increased mortality risk compared to the general population. While anemia commonly occurs in patients with RA and is associated with disease activity in established diseases, the prognostic value of hemoglobin levels at initial diagnosis remains unknown. This study investigated whether baseline hemoglobin levels predict long-term mortality in patients with newly diagnosed RA.MethodsThis retrospective cohort study utilized the TriNetX Analytics Network Platform to identify adult patients with newly diagnosed RA between 2010–2023. Patients were stratified by hemoglobin levels measured within 3 months of diagnosis: low hemoglobin group (< 12 g/dl) vs. control group (≥12 g/dl). Propensity score matching balanced the baseline characteristics and comorbidities. The primary outcome was 3-year overall mortality, with secondary outcomes including major cardiovascular events, stroke, intensive care unit (ICU) admission, severe anemia progression, and pneumonia.ResultsAfter matching, 42,267 patients were included in each group. Low hemoglobin was independently associated with significantly increased 3-year mortality [Hazard ratio (HR): 1.80, 95% confidence interval (CI): 1.69–1.91, p < 0.001], with elevated risk already apparent at 1-year follow-up (HR: 1.90, 95% CI: 1.72–2.10). A clear dose-response relationship emerged: patients with hemoglobin 10–12 g/dl had a 68% increased mortality risk (HR: 1.68), while those with hemoglobin < 10 g/dl faced doubled risk (HR: 2.03). Low hemoglobin levels were also associated with elevated risks for major cardiovascular events (HR: 1.47), stroke (HR: 1.25), severe anemia progression (HR: 2.82), ICU admission (HR: 1.58), and pneumonia (HR: 1.43). The association remained consistent across subgroups and in contemporary cohorts (2018–2023).ConclusionLow hemoglobin levels at RA diagnosis independently predict 3-year mortality with clear dose-response relationships. These findings support the incorporation of hemoglobin assessment into initial RA evaluation algorithms to identify high-risk patients warranting intensified monitoring and aggressive therapeutic intervention.